Research Updates in Neuroimaging Studies of Children Who Stutter - Chang, Soo-Eun (Seminars in Speech and Language, 2014)
In the past two decades, neuroimaging investigations of stuttering have led to important discoveries of structural and functional brain differences in people who stutter, providing significant clues to the neurological basis of stuttering. One major limitation, however, has been that most studies so far have only examined adults who stutter, whose brain and behavior likely would have adopted compensatory reactions to their stuttering; these confounding factors have made interpretations of the findings difficult. Developmental stuttering is a neurodevelopmental condition, and like many other neurodevelopmental disorders, stuttering is associated with an early childhood onset of symptoms and greater incidence in males relative to females. More recent studies have begun to examine children who stutter using various neuroimaging techniques that allow examination of functional neuroanatomy and interaction of major brain areas that differentiate children who stutter compared with age-matched controls. In this article, I review these more recent neuroimaging investigations of children who stutter, in the context of what we know about typical brain development, neuroplasticity, and sex differences relevant to speech and language development. Although the picture is still far from complete, these studies have potential to provide information that can be used as early objective markers, or prognostic indicators, for persistent stuttering in the future. Furthermore, these studies are the first steps in finding potential neural targets for novel therapies that may involve modulating neuroplastic growth conducive to developing and maintaining fluent speech, which can be applied to treatment of young children who stutter.
Keywords: Childhood developmental stuttering; neuroimaging; MRI; fMRI; DTI